A Year after the Outbreak of COVID-19: Applicants' Perception of Higher Education Quality in the Context of Digitalization and Blended Learning - Gavriil A. Agarkov; Daniil G. Sandler; Anastasia D. Sushchenko (National Research Mordova State University, 2021)
Introduction. The forced transition of Russian universities to distance learning in 2020 and accelerated digital transformation of educational processes in higher education are the first effects of the COVID-19 pandemic. A key aspect of measuring higher education quality is the perception of its formats by students as university change agents. The aim of the study is to identify the factors that determine the applicants' positive attitude to learning that includes online elements in the context of the Russian universities' transition to the blended learning model. Materials and Methods. The empirical base of the research includes the results of an online sociological survey conducted among the applicants for Ural Federal University undergraduate and graduate programmes in 2021. The methods of classification, factor analysis, and coefficients of pair correlations were applied. Additionally, for comparison, data from 2015 for a similar sample (1st year bachelor's degree students) were used. Results. Positive attitudes towards online and blended learning are gradually increasing. The factor analysis of data from 2021 showed that applicants who support the online and blended learning include: those aspiring for master's degree upon completing their bachelor's degree course; those who choose their degree field rationally - men who apply for a state-funded education in any Russian university (including participants of federal contests - 'Academic Olympics'). The above groups are formed mainly under the influence of external factors. Another group includes those oriented towards self-realization - women who choose their degree field relying on their personal inclinations for a future profession (the influence of internal factors). Discussion and Conclusion. The research results contribute to the development of scientific ideas about the blended learning model and emphasize the value of institutional research based on feedback from university students for making informed management decisions on change. The materials of the paper will be useful when designing the educational process in the Russian universities' transition to the blended learning model.